Regulatory Vacuum and Clinical Practice Gap in Do Not Resuscitate (DNR) Implementation: A Normative Legal Analysis of Indonesian Health Law - Yuri Sadewo; Yusuf Alim Musthofa Anwar; Arman Lany (Politeknik Siber Cerdika Internasional, 2026)
Background: Some legislation does exist in Indonesia concerning DNR (Do Not Resuscitate), but none offers procedural guidance on whether or how it should be implemented. Objective: This study provides an overview of DNR in Indonesia from a legal standpoint, religious and cultural perspectives, the implementation process in healthcare facilities, determination and documentation process, as well as obstacles during its implementation. Research Method: This research use normative legal sources (Permenkes No. 37/2014, Law No.29/2004about Medical Practice, KODEKI) and secondary source. Which deals with the analysis of legal texts, legal documents as well as normative factors and principles to discern relevant laws. Results: The results show the complexity of the status of DNR which is still a debate in Indonesia. Although DNR is acknowledged as a part of patient rights, details regulation are still considered vague or uncertain (Health Minister Regulation No. 37 year 2014 and Health Law No. 36 year 2009). Other challenges include limited understanding among healthcare providers and the public, and problems in communication with the families of patients. DNR-related decisions are also affected by influence of religious perspectives and cultural norm particularly within the Muslim majority context. Ensuring correct procedures for deciding and recording DNR relies on effective communication, and sufficient documentation. Conclusion: The optimal counterpart is that Indonesia needs and deserves a specific ministerial regulation on DNR, which harmonizes patient autonomy rights with Islamic bioethical principles whilst also providing procedural clarity to eliminate the existing legal ambiguity for health care providers.